Marta Kolářová (ed.): REVOLTA STYLEM. Hudební subkultury mládeže v České republice. [Revolt in Style. Music Youth Subcultures in the Czech Republic.]: Praha: Slon 2012, 264 pp. + photographs. - Jonssonová, Pavla (Lidé města, 2012)
A review of the book by Marta Kolářová.